Racial Diversity in the Workplace - Amundson, Emily J.; Anderson, Stefanie M.; Finley, Alexandra L.; George, Natalie G.; Michalski, Amanda R.; Sweeney, Stephanie C. (My University, 2011)
The U.S. Census Bureau has predicted the number of racial minorities to increase 19% by 2050 which makes workplace diversity a central challenge for businesses in the 21st century (Hostager & Meuse, 2008). While diversity awareness is generally perceived to be beneficial, recent studies have shown that an information overload can cause employees to be apathetic toward diversity (Kalev, Dobbin & Kelly, 2006). However, little is known about how diversity-related messages are received based on the perceived communication variables of the recipient. This study will examine diversity-related messages to determine possible links between these messages and the communication variables of apprehension and competence.
Color poster with text and graphs.
Keywords: Race relations; Work environment; Minorities--Employment; Communication in organizations; Posters